Aspectos da biologia, morfologia e ontogenia da larva de Coryphaeschna perrensi (McLachlan, 1887) (Insecta, Odonata, Aeshnidae), com algumas considerações filogenéticas - Carvalho, Alcimar do Lago (1990)
Aspects of the biology, morphology and ontogeny of the larva of Coryphaeschna perrensi (McLachlan, 1887) (Odonata, Aeshnidae), with some phylogenetic considerations. The larval cycle of the dragonfly Coryphaeschna perrensi was studied based mainly on material collected monthly during two years (1987-1988) in a sand dune swamp located in Maricá, Rio de Janeiro State, Brazil (22º56'S, 42° 50'W). The regular larval development averaged approximately 10 months in the laboratory, having 15 instars (except the prolarva). The last two instars may vary in duration and be enlarged probably to fit the emergence. The flight period is concentrated in seven months, with the peak in February. The morphology of the ultimate instar larva is described and illustrated as well as the morphological changes occurred during the ontogeny since the first instar. Many of the characters described have dif fei·ent states represented. in separate groups of Aeshnidae or correlatives, enabling their polarization based on the ontogeny criterion, contribüting to the establishment of monophyletic groups and their phylogenetic relationship. So, the unique terminyl- latval characters of some species of the genus (premental syines long with the anterior border between the mediyn cleft and the spines armed with piliform setae; prementum long, with the sides of the basal half parallel; posterior border of the head angulate) were taken as synapomorphies which designated Coryphae-schna stricto sensu (C. ingen-s, C. perrensi and C. virititas). Coryphaeschna adnexa is postulated as the the sister groi.tp of ConJPhay-schna stricto sensu with basis on one synapomorphy (two black spots included in the third dark ring ot' the femora). Dyrived states of other characters (movable hooks armed dorsally with a longitudinal row of more than 5 setae; with the molar crest without or with only one tooth m between the teeth a and b), suggest thecondition of the family Aeshnidae.